Identification of a genetically defined ultra-high-risk group in relapsed pediatric T-lymphoblastic leukemia - Richter-Pechańska, Paulina; Kunz, Joachim; Bandapalli, Obul Reddy; Orlova, Elena; Korbel, Jan Oliver; Muckenthaler, Martina; Kulozik, Andreas (Blood cancer journal, 2017)
In the search for genes that define critical steps of relapse in pediatric T-cell acute lymphoblastic leukemia (T-ALL) and can serve as prognostic markers, we performed targeted sequencing of 313 leukemia-related genes in 214 patients: 67 samples collected at the time of relapse and 147 at initial diagnosis. As relapse-specific genetic events, we identified activating mutations in NT5C2 (P=0.0001, Fisher’s exact test), inactivation of TP53 (P=0.0007, Fisher’s exact test) and duplication of chr17:q11.2-24.3 (P=0.0068, Fisher’s exact test) in 32/67 of T-ALL relapse samples. Alterations of TP53 were frequently homozygous events, which significantly correlated with higher rates of copy number alterations in other genes compared with wild-type TP53 (P=0.0004, Mann-Whitney’s test). We subsequently focused on mutations with prognostic impact and identified genes governing DNA integrity (TP53, n=8; USP7, n=4; MSH6, n=4), having key roles in the RAS signaling pathway (KRAS, NRAS, n=8), as well as IL7R (n=4) and CNOT3 (n=4) to be exclusively mutated in fatal relapses. These markers recognize 24/49 patients with a second event. In 17 of these patients with mostly refractory relapse and dire need for efficient treatment, we identified candidate targets for personalized therapy with p53 reactivating compounds, MEK inhibitors or JAK/STAT-inhibitors that may be incorporated in future treatment strategies.